2015
DOI: 10.1002/cssc.201500648
|View full text |Cite
|
Sign up to set email alerts
|

Functionalized Agarose Self‐Healing Ionogels Suitable for Supercapacitors

Abstract: Agarose has been functionalized (acetylated/carbanilated) in an ionic liquid (IL) medium of 1-butyl-3-methylimidazolium acetate at ambient conditions. The acetylated agarose showed a highly hydrophobic nature, whereas the carbanilated agarose could be dissolved in water as well as in the IL medium. Thermoreversible ionogels were obtained by cooling the IL sols of carbanilated agarose at room temperature. The ionogel prepared from a protic-aprotic mixed-IL system (1-butyl-3-methylimidazolium chloride and N-(2-h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
94
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(98 citation statements)
references
References 55 publications
(46 reference statements)
4
94
0
Order By: Relevance
“…A self-healing ionogel from a protic-aprotic mixed-IL system (1-butyl-3-methyl-imidazolium chloride and N-(2-hydroxyethyl) ammonium formate) was successfully prepared. [151] As shown in Figure 6e, the ionogel demonstrated superior self-healing property. The carbanilated agarose ionogels proved suitable as a flexible solid electrolyte for activated-carbon-based supercapacitors.…”
Section: Gpes With Self-healing Abilitymentioning
confidence: 87%
See 1 more Smart Citation
“…A self-healing ionogel from a protic-aprotic mixed-IL system (1-butyl-3-methyl-imidazolium chloride and N-(2-hydroxyethyl) ammonium formate) was successfully prepared. [151] As shown in Figure 6e, the ionogel demonstrated superior self-healing property. The carbanilated agarose ionogels proved suitable as a flexible solid electrolyte for activated-carbon-based supercapacitors.…”
Section: Gpes With Self-healing Abilitymentioning
confidence: 87%
“…Reproduced with permission. [151] To simultaneously realize the self-healability and high stretchability, a polymer electrolyte comprising of polyacrylic acid dual crosslinked by hydrogen bonding and vinyl hybrid silica nanoparticles [154] was developed (Figure 6f). The polymer electrolyte demonstrated tunable ionic conductivity, self-healability, and high stretchability (over 3700% strain).…”
Section: Gpes With Self-healing Abilitymentioning
confidence: 99%
“…[100][101][102] Among these studies, efforts were mainly made concerning the recovery of electrode conductivities and integrity of the overall the configuration. Furthermore, the conventional PVA-based electrolytes with relatively low self-repair capability were frequently employed, which likely limited the overall self-healing performance of the corresponding supercapacitors.…”
Section: Self-healing Abilities In Response To External Mechanical Damentioning
confidence: 99%
“…Consequently, novel polymeric electrolytes which are intrinsically self-healable have been studied further. [100][101][102] Recently, Huang et al has reported a new self-healing electrolyte composed of polyacrylic acid and hybrid vinyl-silica nanoparticles (VSNPs-PAA) (Figure 5b). [103] The PAA polymer chains provided abundant reversible intermolecular hydrogen bonding, while the VSNPs reinforced the mechanical properties and covalently crosslinked the PAA polymer chains.…”
Section: Self-healing Abilities In Response To External Mechanical Damentioning
confidence: 99%
“…[223,224] Extensive work has been done to demonstrate self-healing dielectric material [225] and gels, [226,227] however it is challenging to fabricate a self-healing current collector for the realization of a completely self-healing transparent and stretchable electronic device. It is extremely difficult to achieve selfhealing ability with electronic conductors.…”
Section: Challenges and Outlookmentioning
confidence: 99%